2007
DOI: 10.1590/s0100-39842007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Ressonância magnética no estadiamento dos tumores de colo uterino

Abstract: Cervical cancer is the worldwide leading cause of cancer-related death of women, especially in developing countries. The International Federation of Gynecology and Obstetrics recommends staging during surgery, however, surgical-pathologic staging would not be feasible in cases of more advanced cancers. Generally, in these cases, the staging is performed by means of clinical and gynecological examination and basic imaging studies. However, such an approach fails to demonstrate the actual extent of the disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Accurate and precise dose delivery in HDR MARS for cervical or prostate cancer requires the use of both T1-and T2 -weighted MRI sequences [74][75][76][77][78][79]. Therefore, it is essential to be able to visualize the markers under both T1-and T2-weighted sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and precise dose delivery in HDR MARS for cervical or prostate cancer requires the use of both T1-and T2 -weighted MRI sequences [74][75][76][77][78][79]. Therefore, it is essential to be able to visualize the markers under both T1-and T2-weighted sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, MRI has been described as one of the most appropriate techniques for staging patients with cervical cancer ( 12 ) . Such a method is also described as being the best tool for the acquisition of images during the routine three-dimensional planning, overcoming conventional radiography and the images obtained by means of CT ( 12 - 15 ) . On the other hand, a recent study developed by Viswanathan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ureter can become enveloped by tumors, and this leads to ureterohydronephrosis and eventually kidney failure. The pattern of pelvic dissemination of cervical carcinoma restricts the use of surgical treatment for early forms (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to select patients for curative treatment. Three significant prognostic factors have been identified that may predict a short survival time after percutaneous nephrostomy in patients with advanced-stage cancer: serum albumin, high-grade hydronephrosis, and several three or more events related to malignant dissemination, such as metastases (lung, liver, bones, retroperitoneum, lymph nodes), ascites and pleural effusion (6,8,9).…”
Section: Introductionmentioning
confidence: 99%